Analysis of Mothers Participation in Bringing Their Toddlers to Posyandu in the Banda Raya Community Health Center Area, Banda Aceh City in 2023 - Hariyanti, Susi; Hartono, Risky Kusuma (UI Scholars Hub, 2024)
Background: Integrated Service Post (Posyandu) is a community-sourced health center that belongs to the community and is integrated into the lufe and culture of the community. Lack of community participation in the utilization of Posyandu is one of the problems that hamper the implementation of health services through Posyandu. Domain factors of low participation are from family support, knowledge and attitudes of mothers of toddlers. This support D/S coverage (D is the number of toddlers weighed and S is the number of all toddlers in the area) which is not meeting the national target of 80%. Aims: This study aims to determine the factors associated with the motivation of mothers of toddlers to participate in Posyandu activities in Banda Raya. Methods: This study uses qualitative-quantitative methods with a cross-sectional research design. Results: The results of data processing showed that the characteristics of respondents in the Banda Raya sub-district area had a proportion of maternal participation in the Posyandu category with a less role of 53.41% more dominant that those who participated (46.59%). The factor that influences the level of motivation of mothers of toddlers to Posyandu distance. Community participation in Posyandu activities is only 50% present to the Posyandu, this shows that the target in the health sector has not been achieved. Conclusion: To enhance knowledge about the benefits of Posyandu, the Puskesmas can conduct counselling or health promotion about the benefits of Posyandu so that health workers, community leaders, and related agencies can increase axposure about Posyandu to the community for revitalization.